Phyllanthus capixaba (Phyllanthaceae), a New Species Endemic to Brazil Supported by Macromorphological and Palynological Evidence - Torres, Alícia Marques [UNESP]; Silva, Marcos José Da (American Society of Plant Taxonomists, 2023)
We describe and illustrate Phyllanthus capixaba, a new species hitherto found in the state of Espírito Santo, Brazil. This new species is assigned to P. section Phyllanthus subsect. Phyllanthus and differs from their nearest species P. longipedicellatus by a set of characters such as aspect of branch distribution on the stem, number of pairs of secondary veins per leaf, appearance of tertiary veins and leaf margin, type of stigma, and surface aspect of pollen grains. We present distribution maps, informal conservation status, and phenological data for the new species, an identification key for the Brazilian species of P. subsect. Phyllanthus, and discuss its systematic position in the Phyllanthus section.
Keywords: Espírito Santo; Phyllantheae; Phyllanthus subsect. Phyllanthus